The music of strangers [videorecording (DVD)] : Yo-Yo Ma & the Silk Road Ensemble - Ma, Yo-Yo, 1955-; Ma, Yo-Yo, 1955-; Wu, Man; Wu, Man; Azmeh, Kinan; Azmeh, Kinan; Kalhor, Kayhan; Kalhor, Kayhan; Pato, Cristina, 1980-; Pato, Cristina, 1980- (The Orchard, 2017)
Over the past sixteen years, an extraordinary group of musicians has come together to celebrate the universal power of music. Named for the ancient trade route linking Asia, Africa, and Europe, the Silk Road Ensemble, an international collective created by legendary cellist Yo-Yo Ma, exemplifies music's ability to blur international boundaries, blend disparate cultures, and inspire hope for artists and audiences.